Investigation of Exhaust Emissions Combustion Characteristics in Single Spark Ignition-Engine Matic with Butanol-Gasoline Mixture - Gatot Setyono; Dwi Khusna; Navik Kholili; Lingga Putra Sanjaya; Fajar Galang Argil Putra (Infotekmesin, 2023)
Butanol as a fuel has a high oxygen content, so the combustion process will be more friendly to the environment. In this study, butanol will be mixed with RON-90 gasoline with a capacity of 5% (B5); 7%(B7); 10%(B10); 12%(B12); 15%(B15) and 18%(B18). The engine used is an automatic transmission with a capacity of 109.5cc with a compression ratio of 9.5:1. The test equipment for engine performance and exhaust emissions is the 50L BRT Super-Dyno and EPSG4 Gas Analyzer. The results showed that using B18 fuel for CO exhaust emissions decreased by 44% at an engine speed of 6000rpm. CO2 exhaust emissions have decreased by 47% at 8000rpm engine speed. HC exhaust emissions have decreased by 28% at 9000rpm engine speed. In contrast to NOx emissions, which increased by 22% at 9000rpm engine speed, this was due to the increasing temperature in the combustion chamber.